Correlation Between Laryngeal Sensitivity and Penetration/Aspiration After Stroke - Motonaga Onofri, Suely Mayumi [UNESP]; Cola, Paula Cristina [UNESP]; Berti, Larissa Cristina [UNESP]; Silva, Roberta Gonçalves da [UNESP]; Dantas, Roberto Oliveira (Springer, 2014)
Stroke is the most common neurological disease in adults that is associated with deglutition disorders. The presence of laryngeal sensitivity is very important in developing safe swallowing without risk of pulmonary complications. The aim of this study was to correlate laryngeal sensitivity with laryngeal penetration and tracheal aspiration after swallows of three food consistencies (puree, thickened liquid, and liquid) in poststroke individuals in the late phase. A cross-sectional clinical study was performed with 91 post-ischemic stroke individuals, with oropharyngeal dysphagia, who were in rehabilitation center treatment from 2009 to 2011. They had a mean age of 68.1 years and average time since injury was 22.6 months; 39 had injury to the right hemisphere and 52 had injury to the left hemisphere. All underwent fiberoptic endoscopic evaluation of swallowing and evaluation of laryngeal sensitivity by touching the tip of the endoscope to the arytenoids and aryepiglottic folds. The linear correlation coefficient of Spearman was applied to evaluate the correlation between laryngeal penetration and tracheal aspiration and the presence/absence of laryngeal sensitivity. There was a negative correlation between the observation of penetration and tracheal aspiration and laryngeal sensitivity, with all bolus consistencies (p < 0.001 for aspiration and p a parts per thousand currency sign 0.01 for penetration). The absence of laryngeal sensitivity determines the more frequent findings of penetration and tracheal aspiration. This sensory stimulus in the mucosa of the pharynx and larynx is an essential element for safe swallowing and its deficiency associated with altered motor activity can cause laryngeal penetration and aspiration in poststroke individuals regardless of food consistency.
Keywords: Deglutition disorders; Stroke; Fiberoptic endoscopic evaluation of swallowing